Tingkat Kesukaan dan Kandungan Zat Gizi Cookies Menggunakan Salak Pondoh (Salacca Zalacca Var Pondoh): Level of Favorite and Nutritional Content of Cookies Using Salak Pondoh (Salacca Zalacca Var Pondoh) - Miftana Fitri Aditami; Maryanto, Sugeng; Puji Afiatna (JURNAL GIZI DAN KESEHATAN, 2024)
Salak fruit is perishable, has a limited shelf life, so it is necessary to use appropriate technology to process snake fruit. Salak processed using simple technology that can last quite a long time is making snake fruit flour. Salak flour is processed into raw materials for making processed products into cookies. The aim of this research was to determine the level of preference and nutritional content in processed salak flour cookies. This research uses an experimental design. The sample used was 25 untrained panelists. This was done by making 4 formulations for each product using salak flour F1 (25%: 75%), F2 (50%: 50%), F3 (75%: 25%), F4 (100%) then carried out a liking test . Next,  a  nutrient  content  test  is  carried  out.  Analysis  of  protein,  ash,  water,  fat, carbohydrate and fiber content. The protein content of Pondoh salak cookies is 7.6%, energy 469,615 Kcal, ash 1.60%,  water  content  4.3%,  fat  content  19.9%,  carbohydrates  64.9%,  fiber  content 2.8%. The cookie test results based on the highest level of preference were F2 with average values for color (78.4%), aroma (75.3%), taste (77.6%), texture (74.4%). The most popular salak pondoh cookie formula is formula 2 with an average score of 76.4% in the "Fair" category. ABSTRAK Buah salak bersifat mudah rusak, umur simpan terbatas, sehingga diperlukan penggunaan teknologi yang tepat guna mengolah salak . Oalahan salak diproses dengan menggunakan teknologi sederhana, dapat bertahan cukup lama adalah pembuatan tepung salak. Tepung salak diolah menjadi bahan baku pembuatan produk olahan menjadi cookies. penelitian ini adalah untuk mengetahui tingkat kesukaan dan kandungan zat gizi dalam olahan cookies tepung salak Penelitian ini menggunakan experimental design. Sampel yang digunakan sebanyak  25  panelis  tidak  terlatih.  Dilakukan  dengan  pembuatan  4  formulasi pada masing-masing produk dengan menggunakan tepung salak F1 (25%: 75%), F2 (50% :50%), F3 ( 75% : 25%), F4 ( 100%) kemudian dilakukan uji kesukaan. Selanjutnya dilaksanakan uji kandungan zat gizi. Analisis kandungan kadar protein, abu, air, lemak, karbohidrat dan serat. Kandungan protein cookies salak pondoh yaitu 7.6%, Energi 469.615 Kkal, Abu 1.60%, kadar air 4.3%, kadar lemak 19.9%, karbohidrat 64.9%, kadar serat 2.8%. Hasil uji cookies berdasarkan tingkat kesukaan tertinggi adalah F2 dengan nilai rerata warna (78.4%) , aroma (75.3%), rasa (77.6%) , tekstur (74,4%). Formula cookies salak pondoh yang paling disukai adalah formula 2 dengan nilai rata-rata 76.4% dalam kategori “Cukup”.